Be Credible - Bobkowski, Peter; Younger, Karna; Open Textbook Library (Open Textbook Library, 2018)
The primary audience for this book starts with students in Journalism 302: Infomania, a course we teach at the University of Kansas. When they take this class, these students usually are in their second or third semesters in the William Allen White School of Journalism and Mass Communications. They have varied career aspirations. A few of them want to be "traditional" journalists, writing for online news sites, magazines, or newspapers. Some of them want to be broadcast journalists. Many of them want to work in strategic communications, which encompasses public relations, advertising, marketing, and related fields.
I. Information Workflow -- 1. Be Credible -- 2. Search and Re-Search -- 3. Search More Effectively -- 4. Keep Detailed Research Notes -- 5. Attribute All Sources -- II. Evaluating Information -- 6. Evaluate Information Vigorously -- 7. Go Lateral With Cues and Evidence -- 8. Tap Into a Credibility Network -- 9. Contend With Bias -- III. Information Sources -- 10. Google -- 11. Wikipedia -- 12. Public Records -- 13. Open Records and the Freedom of Information -- 14. News -- 15. Nonprofits -- 16. Scholarly Research -- 17. Data -- 18. Market Research -- 19. Public Companies -- 20. Archives -- 21. Interviews: An Introduction -- 22. Interviews: Conversations with Risk -- 23. Licensing Published Work
In English.
Description based on online resource
Keywords: Communication -- Textbooks